2016
DOI: 10.1088/0964-1726/25/3/035012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of garment design on piezoelectricity harvesting from joint movement

Abstract: The harvesting of piezoelectricity through the human body involves the conversion of mechanical energy, mostly generated by the repeated movements of the body, to electrical energy, irrespective of the time and location. In this research, it was expected that the garment design would play an important role in increasing the efficiency of piezoelectricity scavenged in a garment because the mechanical deformation imposed on the energy harvester could increase through an optimal design configuration for the garme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Piezoelectric elements made of PVDF were also applied in clothing by Yang et al [18]. e view of clothing with a piezoelectric element is shown in the photograph (Figure 3).…”
Section: Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Piezoelectric elements made of PVDF were also applied in clothing by Yang et al [18]. e view of clothing with a piezoelectric element is shown in the photograph (Figure 3).…”
Section: Solutionsmentioning
confidence: 99%
“…A width of the element at the level of 10 mm was selected, in order to ensure the required resistance to repeated mechanical in uences. Yang et al [18] assessed three design variants that differed in terms of their spatial construction. A study carried out with the participation of volunteers demonstrated greater e ciency of piezoelectric elements with an increase in the elasticity of the textile material.…”
Section: Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smart materials are attracting increasing interest especially in the era of the fourth industrial revolution (Industry 4.0) and circular economy. Smart polymer nanocomposites (SPN) which can be derived from shape memory polymer [3][4][5][6], stimuli-active polymers [7], smart electrorheological (ER) and magnetorheological (MR) polymer [8][9][10][11], self-healing polymer [12,13], self-cleaning polymer [14][15][16][17], self-heating polymer [18], self-sensing polymer [19], energy-harvesting and energy storage polymer [20][21][22][23][24][25][26][27] are the latest hot research topics. The addition of nanofiller can increase the performance of the SPN (e.g., shape fixity, shape recovery, self-healing ability) due to their high specific surface area, nucleating effects, reinforcing effects, and inherent functionalities (e.g., thermal conductivity, electrical conductivity) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Hereinto, piezoelectric energy harvesting has attracted more attention than other vibration energy harvesting methods such as using electromagnetic 1 and electrostatic 2 effects due to its advantages including simple structure, scalability and high power output. 3,4 The reported electric power outputs of piezoelectric energy harvesters (PEHs) range from nanowatts to milliwatts, [5][6][7][8] which highly depend on the piezoelectric coupling coefficient of the piezoelectric material. There are dramatic performance improvements in new piezoelectric materials, such as piezoelectric single crystals PZN-PT and PMN-PT, but the wide use of these materials for energy harvesting in the near future is still in question due to their high cost.…”
mentioning
confidence: 99%